Hit identification against peptidyl-prolyl isomerase of Theileria annulata by combined virtual high-throughput screening and molecular dynamics simulation approach - MUTLU, ÖZAL (My University, 2020)
Theileria annulata secretes peptidyl prolyl isomerase enzyme (TaPIN1) to manipulate the host cell oncogenic signaling pathway by disrupting the tumor suppressor F-box and WD repeat domain-containing 7 (FBW7) protein level leading to an increased level of c-Jun proto-oncogene. Buparvaquone is a hydroxynaphthoquinone anti-theilerial drug and has been used to treat theileriosis. However, TaPIN1 contains the A53 P mutation that causes drug resistance. In this study, potential TaPIN1 inhibitors were investigated using a library of naphthoquinone derivatives. Comparative models of mutant (m) and wild type (wt) TaPIN1 were predicted and energy minimization was followed by structure validation. A naphthoquinone (hydroxynaphthalene-1,2-dione, hydroxynaphthalene-1,4-dione) and hydroxynaphthalene-2,3-dione library was screened by Schrödinger Glide HTVS, SP and XP docking methodologies and the docked compounds were ranked by the Glide XP scoring function. The two highest ranked docked compounds Compound 1 (4-hydroxy-3-[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxynaphthalene-1,2-dione) and Compound 2 (6-acetyl-1,4,5,7,8-pentahydroxynaphthalene-2,3-dione) were used for further molecular dynamics (MD) simulation studies. The MD results showed that ligand Compound 1 was located in the active site of both mTaPIN1 and wtTaPIN1 and could be proposed as a potential inhibitor by acting as a substrate antagonist. However, ligand Compound 2 was displaced away from the binding pocket of wtTaPIN1 but was located near the active site binding pocket of mTaPIN1 suggesting that could be selectively evaluated as a potential inhibitor against the mTaPIN1. Compound 1 and Compound 2 ligands are potential inhibitors but Compound 2 is suggested as a better inhibitor for mTaPIN1. These ligands could also further evaluated as potential inhibitors against human peptidyl prolyl isomerase which causes cancer in humans by using the same mechanism as TaPIN1.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Matematik; KİMYA, ORGANİK; MATEMATİK, DİSİPLİNLERARASI UYGULAMALAR; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; MATHEMATICS; MOLECULAR BIOLOGY & GENETICS; CHEMISTRY, ORGANIC; MATHEMATICS, INTERDISCIPLINARY APPLICATIONS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Organik Kimya; Fizik Bilimleri; Hesaplamalı Matematik; Structural Biology; Organic Chemistry; Physical Sciences; Computational Mathematics; Molecular dynamics simulation; Onkogenic signalling patway; Peptidyl prolyl isomerase; Structure-based drug design; Theileria annulata